Long-term Functioning of Allogeneic Islets in Subcutaneous Tissue Pretreated With a Novel Cyclic Peptide Without Immunosuppressive Medication. Issue 3 (March 2018) - Kuwabara, Rei; Hamaguchi, Masahide; Fukuda, Takuya; Sakai, Hiroki; Inui, Makoto; Sakaguchi, Shimon; Iwata, Hiroo
Abstract : Background: There exists a need for a minimally invasive method of islet transplantation without immunosuppressive drugs for the treatment of type 1 diabetes. Methods: In diabetic August Copenhagen Irish rats, an agarose rod containing the cyclic oligopeptide SEK-1005 (agarose-SEK rod) was implanted at 2 dorsal subcutaneous sites. Then these rods were removed, and 1500 islets of Langerhans isolated from Fischer 344 rats were transplanted into each of the pockets. Results: Ten days after implantation of agarose-SEK rods, vascularized pockets were present. Nonfasting blood glucose levels confirmed long-term survival of the allogeneic islet grafts, without immunosuppressive therapy, in 8 of 10 recipients. Flow cytometry and gene expression analyses were performed to investigate the mechanisms underlying graft acceptance. Agarose-SEK rod implantation led to the formation of granulomatous tissue containing regulatory T cells that suppressed immune reactions against the allogeneic islet grafts. Conclusions: These results indicate that the use of an agarose-SEK rod to prevascularize a subcutaneous site may be a useful method for achieving successful allogeneic islet transplantation without immunosuppression. Abstract : There is a strong need for minimally invasive methods of allogeneic islet transplantation without immunosuppression. The authors present data that by the use of an agarose-SEK rod to prevascularize a subcutaneous site this might be achieved. Supplemental digital content is available in the text.